Connectedness Analysis And Investment Strategy Between Stablecoins And International Stock Indices - Ika Maradjabessy; Zaafri Ananto Husodo (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2024)
This research analyzes the dynamic connectedness between fiat-based stablecoins represented by USDC, USDP, and USDT, and gold-based stablecoins represented by DGX and GLC with indices international stocks represented by S&P500, STOXX50, Nikkei225, CSI300, and JKSE using the new method, the DCC-GARCH based dynamic, connected approach. The result shows dynamic connectedness between stablecoins and the stocks indices; this research continues to adopt the DCC-GARCH t-copula method to find investment strategies by calculating the hedging ratio and portfolio weight. Overall, this research finds evidence that portfolio construction can significantly reduce investment risk in all assets used on two assets, Nikkei225 and JKSE. In contrast, the investment strategy with portfolio weights in long positions is suitable for gold-based stablecoins GLC and DGX, where these two assets can be a diversification strategy in compiling a portfolio in long positions with all the assets used.